Towards a workflow management system for service oriented modules. (27th July 2007) - Salayandia, Leonardo; Gates, Ann Q.
With the emergence of service-oriented architectures (SOAs), workflow management systems are being used to create applications from service compositions. Because service compositions may extend across platforms, domains, and virtual organisations, classical implementations of workflow management systems must be extended to address interoperability and reliability. In particular, there is a need to define interoperable and scalable communication mechanisms to support workflows over loosely-coupled environments and to provide support for runtime verification to increase user confidence in workflow behavior. This paper presents a road map towards creating a scientific workflow management system that leverages SOA and runtime verification technologies.